(untitled) (Revista de Culturas y Literaturas Comparadas, 2021)
Putting two works that show, due to the themes they address, several points of contact, also implies treating their connection from a reading focused on the resolutions that each author displays of them. The objective of this approach is to draw attention to the deep meanings that the different approaches to the father figure entail in Jorge Barón Biza’s El desierto y su semilla and Paul Auster’s The Invention of Solitude. In both texts, the condition of the creative possibility of writing is related to the figure of the father. It is from a thematization of this that the respective narratives become feasible, where the dimension of memory and recollection expand towards the present of writing. The experience of fragmentation is reflected in El desierto y su semilla in a particular way for the narrator to perceive the world, gestated by an act of destruction of the father; In The Invention of Solitude, the surprise of the definitive absence places the order of the representation of the paternal bond both of the narrator with his father, and of himself in that role. In both, death appears, summoning loneliness as a space for writing.